Search strategy for the identification of studies exploring influence of household food insecurity on parental feeding behavior for children. - Reis, Heidi; Harmon, Corey (My University, 2023)
This is the full set of search strategies for a scoping review The Association Between Food Insecurity and Parental Feeding Patterns Prior To, and During, the COVID-19 Pandemic. Databases searched include Medline via PubMed, Embase, PsycINFO, Cochrane central, and Scopus.
Protocol for scoping review available from open science framework: osf.io/ksnb5
Keywords: food insecurity; pediatrics